CIPP-Based Evaluation of Badminton Sports Development Program at SLB N Kenteng Banjarnegara - Burhaein, Erick; Eksan, Akhmad (STKIP Paasundan Press, 2025)
The purpose of this study was to evaluate the implementation of the badminton sports development program at SLB N Kenteng Banjarnegara using the CIPP (Context, Input, Process, Product) model. This study is a type of program evaluation research that uses qualitative methods. Data from this study were obtained from a series of semi-structured interviews with research subjects. The population of this study included all individuals who had important roles in the program. The sample of the study consisted of: the principal, 1 sports teacher, 1 non-sports teacher, 3 three students from the badminton sports program, and 1 parent of one of the students. The results of the study showed that: (1) Context evaluation: The program objectives are in line with the school's vision and mission and are fully supported by all elements from within and outside the school. (2) Input evaluation: The facilities and infrastructure for implementing the program are very good, but the quality of the trainers is still low. (3) Process evaluation: The program implementation went well, but student enthusiasm was still unstable. (4) Product evaluation: This program can improve students' badminton and motor skills as well as improve social aspects, self-confidence, and discipline.